Pressure Dependent Mechanical Properties of Thin Films under Uniaxial Strain via the Layer Compression Test - Sinnott, Aaron; Coleman, Jonathan; Cross, Graham; Moebius, Matthias (My University, 2023)
Amorphous materials can exhibit strong nonlinear mechanical properties in comparison to crystalline metals and ceramics, largely due to their non equilibrium state which depends on the means of sample preparation history. For example, glassy polymer structure is highly dependent on the speed of quenching through the glass transition which determines the degree of free volume within the system. Porous materials and composites often exhibit similar void space dependencies on preparation, for example with extrusion or spraying parameters. This can lead to variations in mechanical response of a material with strain, as the material density will change due to the alteration of free volume. While this remains challenging to quantifying comprehensively in bulk materials, it remains almost completely unaddressed in the case of thin films where current mechanical testing techniques struggle to apply and monitor well characterised application of stress and strain required to adequately probe such effects. Given the central importance of thin film materials across many modern technologies, ranging from semiconductors to medical devices and sensors, there exists a need to adequately monitor and describe changes in amorphous thin film properties under a changing mechanical state. In this work we present the effect of elasticity and yield pressure dependence during aligned flat punch nanoindentation of amorphous thin films in the layer compression test. Supported by finite element simulations of a pressure dependent material, we show continuous in-situ stiffening of polystyrene and sprayed graphene nanosheet networks films throughout uniaxial strain compression. We also demonstrate yielding of thin film PMMA in this geometry through the injection of additional shear within the layer compression test, which may allow exploration of yield in thin films of materials with highly pressure sensitive yield surfaces.
PUBLISHED
Keywords: Nanoscience & Materials; Applied physics; FILMS; Materials Sciences; Nanomechanics; Nanotechnology; Physics; Surface and interface physics; THIN FILM